1958
DOI: 10.1099/00221287-18-2-364
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity Changes in Suspensions of Gram-Positive Bacteria in Relation to Osmotic Pressure

Abstract: The turbidity of suspensions of Gram-negative micro-organisms is known to be influenced by the tonicity of the suspending medium. In contrast to this, suspensions of Gram-positive micro-organisms have the same optical density in 0.2 M-NaC1 as in distilled water. At higher salt concentrations, however, occasionally some batches were found to display changes in turbidity. Correlation was shown between the concentration of the amino acid pool of the organisms and their response to changes in osmotic pressure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1959
1959
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Conversely, protoplast contraction results in an increase in optical density. A similar dependence of optical density on volume has been found for intact bacteria (Mitchell and Moyle, 1956;Kuczynski-Halmann, Avi-Dor, and Mager, 1958), rat liver mitochondria (Tedeschi and Harris, 1958), and erythrocytes (Wilbur and Collier, 1943).…”
Section: Resultssupporting
confidence: 77%
“…Conversely, protoplast contraction results in an increase in optical density. A similar dependence of optical density on volume has been found for intact bacteria (Mitchell and Moyle, 1956;Kuczynski-Halmann, Avi-Dor, and Mager, 1958), rat liver mitochondria (Tedeschi and Harris, 1958), and erythrocytes (Wilbur and Collier, 1943).…”
Section: Resultssupporting
confidence: 77%
“…Potassium, which is ordinarily present in these cells at a concentration of 0.2 M, is lost from the cells when they are washed with 0.05 M MgSO4 (V. S. Srivastava, P. T. S. Wong, and R. A. MacLeod, unpublished data). As suggested by Kuczynski et al (9) in connection with gram-positive bacteria which have lost their amino acid pool, perhaps cells which have lost small molecules have a lower internal osmotic pressure and, hence, are able to contract to a gater extent than cells with their intracellular solutes intact.…”
Section: Discussionmentioning
confidence: 95%
“…Gram-positive bacteria ordinarily do not show 1 From a thesis submitted by Tibor I. Matula in partial fulfillment of the requirements for the Ph.D. degree at McGill University, May 1967. A preliminary report of these findings was presented at such optical effects, although after incubation in phosphate buffer followed by washing in distilled water, the cells of a number of species of grampositive bacteria became susceptible to optical changes comparable to those of gram-negative organisms (6,9). Our interest in the mechanism of these optical effects was aroused when we observed that suspensions of a marine pseudomonad showed optical changes typical of those of other gram-negative bacteria upon the addition of NaCl to the suspending medium.…”
mentioning
confidence: 99%
“…arises from the presence within the pro toplast of a high osmotic concentration of certain solutes [Mitchell (45) ; (25,48,49,50); Gale (148, 149»). The internal pressure must be created by the so-called active transport systems, that is to say, by the coupling of certain chemical bond exchanges of metabolism to the uptake, through the osmotic link, of nutrients [e.g., amino acids (40,48,149,150) ; phosphate (45,151)) which are accumulated in the protoplast. .…”
Section: Physiologymentioning
confidence: 99%